Arylamine N-acetyltransferases 1 - Sim, Edith (Henry Stewart Talks, 2007)
Mechanism of action, Reaction substrates, Isoform substrate profiles, Isoenzymes NAT1 and NAT2, Regulation of gene expression, Pharmacogenetics, Phenotype/genotype correlation, Ethnic variation, Transgenic mouse models, NAT protein structures, NAT as a biomarker in breast cancer, NAT inhibitors as diagnostic agents, NAT in mycobacteria, NAT inhibitors as an approach to potential anti-tubercular agents
Updated at 2016/07/28